Traditional uses and practices of edible cultivated Allium species (fam. Amaryllidaceae) in Sweden - Erik de Vahl; Ingvar Svanberg (BMC, 2022)
Abstract Background While the utilitarian crops grown in vicarage gardens in pre-industrial Sweden have been fairly well documented, our knowledge of plants cultivated for food among the peasants and crofters is limited. Nevertheless, garden vegetables and herbs played a much more important role in the diet of the rural population from a nutritional point of view than, say, wild plants, at least in the southern part of the country. This study aims to explore the importance of edible cultivated onions, Allium, and their various cultivars and old landraces that were once-and in some cases still are-grown in home gardens. Methods This study is based on documentation collected from national surveys carried out by the Swedish National Programme for Diversity of Cultivated Plants (POM), and from an intense search for references to the cultivation and use of carious onions in the historic garden literature, herbals and ethnographic records found in responses to folklife questionnaires. Results The rural population in pre-industrial Sweden cultivated various kinds of bulb onions. They are known under various folk names, although their taxonomic affiliation has been unclear. Many folk taxa have been classified and named by their use, while other names refer to the practices associated with the cultivation system. These onions were often described as especially well suited for storage over winter. Onions have had a wide range of uses in Sweden. In some parts of Sweden, onions were eaten during church service in order to keep the churchgoers awake. Several types of onion have commonly been used as condiments in pickled herring dishes, spreads, sauces, foods made of blood and offal, dumplings, meat dishes and soups. Garlic was used for medicinal and magical purposes, as well as for ethnoveterinary medicine. Onion skins have traditionally been used for dyeing eggs at Easter. Conclusion Genetic diversity of vegetables and garden crops represents a critical resource to achieve and maintain global food security. Therefore, ethnobiologists studying agricultural societies should place more focus on old landraces, cultivars and cultivation practices in order to understand the importance of garden crops for a society. They are an important element of sustainability.